ISIS and Al-Qaeda as strategies and political imaginaries in Africa: a comparison between Boko Haram and Al-Qaeda in the Islamic Maghreb - Raineri, Luca (Civil wars, 2017)
By analysing Boko Haram and Al-Qaeda in the Islamic Maghreb, this article argues that ascriptions to international jihadist brands are linked to local movements’ political economy and geopolitical imaginaries, and, therefore, driven more by contingent strategic considerations rather than by ideological motives. Consequently, three sets of evidence are discussed, by drawing also on fieldwork conducted in Mali and Niger from 2013 to 2016: the discourses of these actors; their political economies; their use of political violence. In conclusion, we analyse the ‘territorialised-deterritorialised cleavage’ and argue that this has greater heuristic value to understand African ‘jihadisms’ than existing categorisations of political violence.